Early-Career Complementologists (ECCO) – Past achievements and future directions. (November 2022) - Poppelaars, Felix; Gaya da Costa, Mariana; Inkeri Lokki, A.; Mallah, Khalil; Nord, Dianna; Reddaway, Jack; Schäfer, Nicole
Abstract: The Early-Career Complementologists (ECCO) is a task force that was established, in close collaboration with the European Complement Network (ECN) and the International Complement Society (ICS), with the specific mission to support and connect early-career researchers (ECRs) in the complement field. ECRs are junior scientists at the early stages of their training which include undergraduate as well as graduate students, Ph.D. graduates, and post-doctoral fellows. This unique population within the scientific community represents the next generation of scientific leaders. However, ECRs are faced with key challenges and the COVID-19 pandemic has disproportionately impacted them. In this paper, we provide further insight into specific needs and challenges of ECRs in the complement field. We surveyed 52 ECRs in the complement field and assessed their perceptions of 1) mentor and peer support, 2) working conditions as well as 3) career interests and prospects. Furthermore, we review the various activities carried out by ECCO over the past years such as our social media presence, social events, and newly-created awards. We also discuss the future activities and events to be carried out by ECCO. Through these initiatives and activities, ECCO strives to boost collaborations between ECRs, provide recognition, and improve the visibility of their work. In addition, continuous joint efforts must also be made by the scientific community, research institutes, and funding organizations to nurture and invest in ECRs. Highlights: Early-career researchers (ECRs) represent the transition phase between being a student and having a senior academic position. The Early-Career Complementologists (ECCO) is an initiative to support ECRs in the complement field. We conducted a survey among 52 ECRs in the complement field to identify their needs and challenges. The results from the ECCO survey will be used for analysis, reporting, and future directions.